Minimal impact of feed intolerance during therapeutic hypothermia for hypoxic ischaemic encephalopathy in a South African cohort with a standardised feeding regimen - Samaai, Ilhaam; Pepper, Michael S.; Pillay, Shakti; Horn, Alan R. (Frontiers in Pediatrics, 2025)
IntroductionEnteral feeding during therapeutic hypothermia (TH) for neonatal hypoxic ischaemic encephalopathy (HIE), is beneficial, but there is insufficient evidence to guide timing and feed advancement strategies. The aim of this study was to describe feed tolerance and outcomes after TH with a standardized progressive early enteral feeding regimen.MethodsData were retrospectively reviewed from neonates with HIE who were treated with TH for HIE in the Groote Schuur Hospital (GSH) Neonatal intensive care unit (NICU), between 1 July 2019 and 31 October 2022. Enteral feeds were commenced at age 12–24 h and incremented daily if tolerated, at 12 ml/kg/day for the first 3 days and 24 ml/kg thereafter. Nutritional, morbidity and mortality outcomes were compared between neonates with and without early feed intolerance (EFI) by the fourth day of life.ResultsThirty three percent (16/48) developed EFI. However, by day six the median (IQR) enteral volumes were, 120 (110–120) and 90 (90–99), in neonates without and with feed intolerance respectively. There were no differences in resuscitation characteristics. Neonates with EFI, had higher HIE grades, more amplitude integrated electro-encephalograph (aEEG) suppression at 48 h (p = 0.002), later attainment of full nutritive sucking or cup feeds (p < 0.001) and longer hospital stays (p = 0.038). There were no differences in other morbidities. Mortality was 6% and necrotising enterocolitis did not occur in either group.ConclusionsEarly feeding was generally well tolerated. Feed intolerance was more frequent in neonates with severe HIE, but most neonates achieved independence from IV fluids by day six.